2003
DOI: 10.18806/tesl.v21i1.271
|View full text |Cite
|
Sign up to set email alerts
|

Variability of ESL Learners' Acquisition of Cognitive Academic Language Proficiency: What Can We Learn From Achievement Measures?

Abstract: With the revamping of the Canada Immigration Act in 1985, the demographic profile of new arrivals to Canada took a marked shift to place a priority on better educated, business-class immigrants. Most of these immigrants are from the Pacific Rim, and they have high expectations for the academic achievement of their children in the Canadian school system. The purpose of this study was to look at age on arrival and first-language proficiency of these children, as these factors interact with instructed ESL support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Learners who arrive at a younger age struggle more to develop their academic language than older-arriving learners (Roessingh & Kover, 2003). These researchers found that older learners were able to transfer language and literacy concepts that they had already developed in their first language.…”
Section: Discussionmentioning
confidence: 97%
“…Learners who arrive at a younger age struggle more to develop their academic language than older-arriving learners (Roessingh & Kover, 2003). These researchers found that older learners were able to transfer language and literacy concepts that they had already developed in their first language.…”
Section: Discussionmentioning
confidence: 97%
“…As the school's instruction language is English, it is not suprising that children with worse command of English have difficulties (Schwartz & Stiefel, 2006). ESL learners routinely struggle with acquiring the competence in the language of instruction (Roessingh & Kover, 2003). Combined with gender and age differences, these suggest that the composition of kindergarten classes is an important factor to be considered in planning educational activities.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, students who are literate in their L1 generally make faster progress in L2 acquisition (Bernhardt & Kamil, 1995;O'Malley & Chamot, 1990) and do better on tests (Cummins, 1982(Cummins, , 1983 than those without L1 literacy, i.e., ELD students. Length of stay in Canada in relation to the age when students are immersed in English (Collier, 1987(Collier, , 1988Cummins, 1981;DiCerbo, 2000;Roessingh & Kover, 2003) and reading/writing at home (Collier, 1992;Krashen, 1987Krashen, , 2007 have also been shown to have a significant impact on academic learning and success. In addition, research has indicated that cultural capital, including prior knowledge and language skills, acts as a filter in disadvantaging L2 students who do not possess English language proficiency (Garcia & Gopal, 2003).…”
Section: Introductionmentioning
confidence: 99%